The Federal Democratic Republic of Ethiopia : Poverty Reduction Strategy Paper: Growth and Transformation Plan 2010/11-2014/15: Volume I. (IMF Staff Country Reports; Country Report, 2011)
This strategic paper discusses Ethiopia's growth and transformation plan (GTP) for the periods 2010/2011 and 2014/2015. The Ethiopian government's main development agenda has been poverty eradication. The government has designed, and is implementing, strategies, policies, and plans to guide and manage the overall development of the country accordingly. The GTP envisages that, besides maintaining a fast-growing economy, better results will be realized in all sectors. Implementation of the GTP requires mobilization of financial and human resources, especially for infrastructure development.